Mapping stakeholders' viewpoints on innovation along a livestock value chain: a Q method application. Issue 2 (17th February 2021) - Govoeyi, Benoît; Ahounou, Serge G.; Kiki, Pascal S.; Dotché, Ignace O.; Moula, Nassim; Youssao Abdou Karim, Issaka; Antoine-Moussiaux, Nicolas
ABSTRACT: Innovating is vital to farmers in sub-Saharan Africa, to adapt to challenges and benefit from opportunities. Stakeholders' decisions to engage in innovation programmes are influenced by their perceptions. This article uses the Q-method application to investigate these perceptions along the swine value chain in Benin. Fifty-five statements were established with local stakeholders and then graded by 25 interviewees on an 11-grade scale. Three main discourses were identified: an optimistic discourse tied to an endogenous vision of innovation, and a pessimistic one to a top-down, exogenous vision. A third discourse highlighted more nuanced redistributive effects of innovation. Innovation platform projects, stimulating local innovation, should rest on and reinforce the first optimistic discourse.